The role of Tumour Necrosis Factor Alpha (TNF-ALPHA) serum level and genetic polymorphisms with cutaneous leishmania infections - Eman Salman Khamaes,; Ali Hafedh Abbas,; Nagham Yaseenm Al-Bayati, (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the role of tumour necrosis factor alpha level and genotyping in susceptibility to leishmaniasis. Method: The case-control study was conducted from March to July 2021 at Baqubah Teaching Hospital, Diyala, Iraq, and comprised patients of cutaneous leishmaniasis in group A and healthy controls in group B. The serum level and single nucleotide polymorphisms of tumour necrosis factor-alpha rs41297589 and rs1800629 were compared between the groups. Data was analysed using SPSS 28. Results: Of the 150 subjects, there were 75(50%) in group A; 39(52%) males and 36(48%) females with mean age 23.91±13.14 years. The remaining 75(50%) subjects were in group B; 38(50.7%) males and 37(49.3%) females with mean age 22.84±4.35 years. Tumour necrosis factor-alpha level in group A was 55.81±39.64 compared to 7.51±3.61 in group B (p<0.05). Single nucleotide polymorphism rs41297589 showed that TT genotype and T allele were significantly increased in group A compared to group B (p<0.05), while rs1800629 showed that GA genotype and A allele were significantly increased in group A compared to group B (p<0.05). The serum level of tumour necrosis factoralpha in group A was increased in TT genotype compared to other genotypes at rs41297589, and in GA genotype compared to other genotypes at rs1800629 (p<0.05). Conclusions: There was a significant association between tumour necrosis factor-alpha serum level and genetic polymorphisms rs41297589 and rs1800629 among cutaneous leishmaniasis patients. Keywords: Polymorphism, Nucleotide, Alleles, Psychodidae, Leishmania, Parasites, Cutaneous, Nucleotides.